Unfired Clay-Cork Granules Bricks Reinforced with Natural Stabilizers: Thermomechanical Characteristics Assessment - Fatima Zohra El Wardi; Sara Ladouy; Abdelhamid Khabbazi; Khalid Ibaaz; Asmae Khaldoun (Civil Engineering Journal, 2021)
Cork is an ecological, natural, and renewable additive, an excellent thermal and acoustic insulator. All these attributes encourage its use in the building sector. Adding this additive to the Earth leads to a more lightweight composite with better thermal performance than the Earth alone. Unfortunately, the mechanical performance of this composite is degraded significantly, limiting its use in construction applications. The authors propose in this study to stabilize the clay-cork composite using natural stabilizers. A chemical stabilization was tested using local quick-lime, in addition to a physical stabilization using natural sheep-wool fibers. The primary purpose is to propose eco-friendly construction material with enhanced thermal and mechanical properties and the lowest environmental impact based on local and ecological raw materials to encourage more sustainable and low-energy constructions. First, physicochemical and mineralogical characterization of used clay was investigated. Then, an experimental investigation was conducted to identify the lime content that allows the optimal stabilization for the used clay. In this context, many different specimens of Bensmim soil stabilized with lime at six many contents 0, 10, 20, 30, 40, 50, and 70% were prepared and tested. The obtained results showed that the optimal lime content for the better stabilization of the used soil is about 30%. Next, an experimental study of thermomechanical properties was conducted on unfired clay bricks mixed with expended cork granules and stabilized by the addition of variable proportions of quick-lime 0, 10 and 30% and sheep-wool fibers 0, 1, and 2%. The mechanical performance of the specimens was investigated in terms of compressive and flexural strengths. At the same time, thermal quality was qualified through evaluating thermal conductivity using the steady-state Asymmetrical Hot Plate test method. The very encouraging experimental findings showed that using lime and sheep-wool fibers at the studied addition content resulted in lightweight composites with lower thermal conductivity and higher compressive and flexural strength than reference samples. The highest thermomechanical performances are obtained with clay-cork blocks reinforced with 30% lime content and 2% sheep-wool fibers. This block recorded values of 583 kg/m3, 0.155 W/m/K, 1.55 MPa, and 3.91 MPa, for bulk density, thermal conductivity, flexural and compressive strength respectively, compared to 765 kg/m3, 0.238 W/m/K, 0.96 MPa and 2.29 MPa for control samples. New material presents lightweight material for both improved thermal and mechanical qualities encouraging its use in building applications. Doi: 10.28991/cej-2021-03091778 Full Text: PDF